Understanding Social Performance: A 'Practice Drift' at the Frontline of Microfinance Institutions in Bangladesh. Issue 3 (6th March 2018) - Maîtrot, Mathilde
ABSTRACT: This article examines the role of microfinance staff and procedures in enabling microfinance's social mission. It does so primarily through studying institutional ruling relations and practices in rural Bangladesh. Attempting to move away from the linear and deterministic approaches of impact studies, it ethnographically scrutinizes the everyday practices of implementers. Findings point to the emergence of systemic practices that jeopardize microfinance institutions' potential to perform their social mission. These include low client‐selection standards, hard selling of loans and forceful loan renewal, little follow‐up on loan use, and abusive and violent client‐retention and repayment‐collection strategies. This is conceptualized as a 'practice drift' as distinct from the commonly reported 'mission drift'. Rather than stemming from planned, top‐down changes in institutional mission and strategy, practice drift emerges from a displacement of decision‐making processes to the branches. The article argues that observed changes in microfinance practice are enabled by decentralized structures and management systems that leave the choice of tactics used to achieve targets to the discretion of field staff.